Hypercholesterolemia During Pregnancy is Caused by Increased Endogenous Cholesterol Synthesis: Let’s Use it for Screening of Familial Hypercholesterolemias Too! - Hyánek, Josef; Pehal, František; Dubská, Ladislava; Míková, Blanka; Gombíková, Lada; Kubu, Stanislav; Halácková, Petra; Feyreisl, Jaroslav; Táborský, Ludek (Journal of Nutritional Therapeutics, 2018)
Aims: To demonstrate the origin and the diagnostic significance of non-cholesterol sterols (NCSs) in healthy pregnant women with gestational hypercholesterolemia. Patients and Methods: Based on a total of 21,000 clinical biochemistry tests of healthy pregnant women with hypercholesterolemia observed during pregnancy, a group of 84 women with TC (total cholesterol) >7.0 mmol/L was recruited to analyze their NCSs using Gas Chromatography–Mass Spectrometry. The NCSs under examination comprised lathosterol (Lat) and desmosterol (Des) as markers of endogenous cholesterol synthesis, and campesterol (Cam) and sitosterol (Sit) as markers for intestinal absorption. Results: In the total of 21,000 pregnant women, the median values were: TC 6.8 mol/l, LDL-C 4.6 mmol/L, and HDL-C 2.2 mmol/L. In the testing group of 84 women, the average values were: Lat 7.8+/-1.7 μmol/L, Des 4.7+/-0.9 μmol/L, Cam 9.8+/-2.6 μmol/L, and Sit 9.6 +/-3.8 μmol/L. Lat was found to correlate with TC (r = 0.53), LDL-C (r = 0.36), and non-HDL-C (r = 0.35). No such correlations were observed for Sit (r = 0.162) or Cam (r = 0.153). Conclusion: Our findings show that the high incidence of hypercholesterolemia during pregnancy is caused by increased endogenous cholesterol synthesis via lathosterol. The enormous rise of TC levels during pregnancy can be effectively used to detect familial hypercholesterolemia in women.